Pelatihan Pengolahan Air Kelapa menjadi Nata de Coco di Desa Sungai Kakap, Kalimantan Barat - Rahmawati Rahmawati; Siti Khotimah; Mukarlina Mukarlina; Zulfa Zakiah; Firman Saputra; Masnur Turnip; Aotza Lisandra (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
Old coconut water is often discarded by the community as waste. This community service activity aimed to provide training on processing coconut water into nata de coco for the members of the Family Welfare Empowerment Group (PKK) in Sungai Kakap Village, Kubu Raya Regency, West Kalimantan. The implementation of this community service program consisted of several stages, including dissemination/socialization, hands-on practice, and discussion sessions. The activity began with the preparation of tools and materials at the Biology Laboratory, Faculty of Mathematics and Natural Sciences, Tanjungpura University (FMIPA UNTAN), followed by a field visit to the target village, participant gathering, socialization of nata de coco production materials, joint practice with workshop participants, and a discussion session. The nata de coco production training was successfully carried out at the Sungai Kakap Village Office, West Kalimantan. Based on the questionnaire results, the PKK members stated that the activity was beneficial, and many expressed their interest in applying the process and producing nata de coco for personal consumption as well as for potential commercialization.